Pengembangan Bahan Ajar Flora Berbais Canva Mata Pelajaran IPAS di SDN 1 Sumberjo Kulon Ngunut Tulungagung - Friska Emilya Ardani; Nourma Oktaviarini (Departement of Mathematics Education, 2024)
Learning media has a very important position and has a big influence on the learning process, including creating an active, creative, innovative, effective and enjoyable learning atmosphere. Teachers are required to create learning media that can motivate students to be more active in learning. Because, without a variety of media, learning activities will not run effectively. The right strategy for studying and understanding Biodiversity is in the Social Sciences subject about the Distribution of Flora and Fauna in Indonesia by using teaching materials. This research aims to develop teaching materials using children's games on operations to count numbers up to three digits for class V elementary school students. This research is research that uses the ADDIE development model. There are 5 main stages in this research consisting of analysis, design, development, implementation, and evaluation stages. The results of this research are to produce products in the form of teaching materials for students and teachers for the learning and teaching process. The product was validated by material experts, media experts and the product was revised based on the validator's suggestions until it was declared suitable for testing. Results of interviews with students at Sumberjo Kulon 1 Elementary School, Ngumut, Tulungagung in small group trials conducted on 5 class V students with a result of 83%, while with the large group the percentage was 88%. Based on the development process starting from validation from material experts, media experts to the results of small and large group trials, overall it was concluded that this children's game-based teaching material product in the form of books is very good to use.